Dysregulation of prefrontal parvalbumin interneurons leads to adult aggression induced by social isolation stress during adolescence - Li, Xinyang; Sun, Huan; Zhu, Yuanyuan; Wang, Feidi; Wang, Xiaodan; Han, Lin; Cui, Dongqi; Luo, Danlei; Zhai, Yifang; Zhuo, Lixia; Xu, Xiangzhao; Yang, Jian; et al. (Frontiers in Molecular Neuroscience, 2022)
Social isolation during the juvenile stage results in structural and functional impairment of the brain and deviant adult aggression. However, the specific subregions and cell types that underpin this deviant behavior are still largely unknown. Here, we found that adolescent social isolation led to a shortened latency to attack onset and extended the average attack time, accompanied by anxiety-like behavior and deficits in social preference in adult mice. However, when exposed to social isolation during adulthood, the mice did not show these phenotypes. We also found that the structural plasticity of prefrontal pyramidal neurons, including the dendritic complexity and spine ratio, was impaired in mice exposed to adolescent social isolation. The parvalbumin (PV) interneurons in the prefrontal infralimbic cortex (IL) are highly vulnerable to juvenile social isolation and exhibit decreased cell numbers and reduced activation in adulthood. Moreover, chemogenetic inactivation of IL-PV interneurons can mimic juvenile social isolation-induced deviant aggression and social preference. Conversely, artificial activation of IL-PV interneurons significantly attenuated deviant aggression and rescued social preference during adulthood in mice exposed to adolescent social isolation. These findings implicate juvenile social isolation-induced damage to IL-PV interneurons in long-term aggressive behavior in adulthood.